2014
DOI: 10.1186/2049-1891-5-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary defatted diatom biomass on egg production and quality of laying hens

Abstract: BackgroundThis study was to determine if feeding laying hens with defatted diatom microalgal biomass (DFA) from biofuel production affected their egg production and health status.MethodsFive replicates of 5 individually caged ISA Babcock White leghorn hens were fed 4 diets, including a corn-soybean meal control diet, a diet containing 7.5% DFA substituting for soybean meal, and diets containing 7.5% or 15% DFA substituting for corn and soybean meal. Body weights, feed intake, feed conversion ratio (FCR), rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 31 publications
(38 reference statements)
2
12
0
Order By: Relevance
“…Vidyashankar et al (2014) reported adverse effects of high ash content in animals fed 20 % defatted biomass of a S. dimorphus strain as a single dose. Similar observations have been made by Leng et al (2014) with white leghorn laying hens when fed 15 % defatted diatom (Staurosira sp.) biomass.…”
Section: Discussionsupporting
confidence: 83%
“…Vidyashankar et al (2014) reported adverse effects of high ash content in animals fed 20 % defatted biomass of a S. dimorphus strain as a single dose. Similar observations have been made by Leng et al (2014) with white leghorn laying hens when fed 15 % defatted diatom (Staurosira sp.) biomass.…”
Section: Discussionsupporting
confidence: 83%
“…The use of yellow lupin seed meal in the feeding mixture resulted in a more distinct yellow/red egg yolk (Dvorak et al 2007). In addition, defatted diatom microalgal biomass diet in laying hens increased the egg albumen weight and height compared with 7.5% defatted diatom microalgal biomass diets (Leng et al 2014). …”
Section: Discussionmentioning
confidence: 93%
“…Moreover, Spirulina enhances to increase feed intake without toxicity [26,27,28,29,30]. Further research is needed for the confirmation about of economic and feasibility to recommend in diets of different poultry species [31][32][33].…”
Section: Mortality and Economic Analysis Of Using Spirulinamentioning
confidence: 99%